The Effect of a Combination between In-Water Recompression (IWR) and Leg Posterior Massage Toward Neurotic Symptom for Those Who Suffer Decompression - Nurfantri Nurfantri (LPPM STIKes Karya Kesehatan, 2021)
Indonesia has lots of marine biota and has been associated with coral reefs such as sponges, sea urchins, crustaceans, mollusks, and more. In addition, fishery products of Indonesian’s biota are the biggest contributor for marine’s fishery in the world (Burke, 2001). Saponda Laut is an area at Toronipa beach, Konawe. It is inhabited by 90 households and their economic income is from coral reefs and other biota. Most of the fishermen don’t care about the safety stop in a rescue process causes them suffer decompression. This study aims to obtain the effect of a combination between in-water recompression and leg posterior massage toward neurotic symptom for traditional divers who suffer decompression at Saponda Laut Island. This is an experiment study uses post-test only control group design to obtain the effect of a combination between in-water recompression and leg posterior massage toward neurotic symptoms for those traditional divers who suffer decompression at Saponda Laut island. Data analysis were done by observing the changes happened on patients after teaching them about how to take a pee, join paint, numbness, and move weak extremist. There is a meaningful difference showed by treatment group than those who are in control group. The patients who suffer decompression in treatment group have been treated with an intervention uses a combination between in-water recompression and leg posterior massage with P value = 0.025.